Chemical constituents from the stems of Acanthopanax senticosus with their cytotoxic activities. Issue 7 (3rd July 2022) - Chen, Xian-Hua; Zhao, Yu-Ying; Wang, Qi; Li, Zhi-Ling; Li, Feng-Xia; Tan, Hong-Yu; Huang, Yue-Yue
Abstract: A new coumestan named 7, 5'-dihydroxy-4'-(3''-hydroxy-3''-methyl- trans -isobut-1''-enyl) coumestan (1 ), together with five known compounds (2–6 ), was isolated from the EtOAc-soluble extract of the stems of Acanthopanax senticosus . Their structures were elucidated based on extensive spectroscopic analyses. All the isolates were evaluated for in vitro cytotoxic activities against four human cancer cells including HepG2, A549, HeLa and MCF-7. Among them, the new compound 1 was found to exhibit significant cytotoxic activity on HeLa cells with IC50 value of 6.5 μM. Abstract : UF0001